A global comparison of DNA sequences of Pelopidas (Lepidoptera: Hesperiidae) reveals discordance between morphological and genetic data, and an insular 'ghost' population. Issue 1 (13th September 2020) - Goonesekera, Kshanika; Lee, Patricia L. M.; Van Der Poorten, George; Ranawaka, Gaya
Abstract: The Pelopidas are a widely distributed genus of hesperiids ranging from the Afrotropical to Australasia. Based on traditional classification, four species are recorded from Sri Lanka: Pelopidas agna, P. mathias, P. subochracea and P. conjuncta . The aim is to test the taxonomic hypotheses of the Sri Lankan Pelopidas as they are currently recognised based on morphology. We achieve this by analysing the phylogenetic relationships among the Pelopidas as well as between the Pelopidas and tribe Baorini both inside and outside of Sri Lanka. We used DNA sequence data from the cytochrome oxidase c subunit I ( COI ) "barcode" region and two nuclear DNA regions, elongation factor 1‐ α ( EF1‐α ) and wingless ( Wgl ) collected for Sri Lankan Pelopidas and combined with all available Pelopidas sequence data from public databases. The reconstructed phylogeny showed that P. mathias, P. agna and P. conjuncta were not monophyletic. Additionally, P. agna in Sri Lanka may now be a hybrid population that retains the P. agna morphology but possesses the mitochondrial DNA of P. mathias (termed a 'ghost' population). Finally, two lineages of P. conjuncta were identified in Sri Lanka, appearing more closely related to other species of Pelopidas than to each other. This study demonstrates the phylogenetic complexity within the Pelopidas and the uniqueness of the Sri Lankan Pelopidas that have not been previously appreciated. This new knowledge is important in planning conservation management and may also guide future work on the potential mechanisms of evolutionary diversification of island butterflies. Abstract : A more complete phylogeny of the skipper butterfly tribe Baorini is provided with a better understanding of the taxonomic status, genetic identification and phylogenetic relationships of the Pelopidas with implications for conservation . The phylogenetic analysis showed that P. agna, P. mathias and P. conjuncta were not monophyletic clades. The current population of P. agna in Sri Lanka appear to be a 'ghost' population, that retains the P. agna morphology but possesses the mitochondrial DNA of P. mathias . Two lineages of P. conjuncta are present in Sri Lanka, more closely related to sister species, P. thrax, P. jansonis and P. lyelli, than to each other.